Foreign relations law - McLachlan, Campbell (Cambridge University Press, 2014)
"[E]very international dispute is of a political character, if by that is meant that it is of importance to the State in question. Thus viewed, the proposition that some legal questions are political is an understatement of what is believed to be the true position. The State is a political institution, and all questions which affect it as a whole, in particular in its relations with other States, are therefore political"-- Provided by publisher.